Vestibular neuritis presenting in pregnancy: case report of rare entity and treatment options - Gökgöz, Mert Cemal; Binar, Murat; Arslan, Fatih; Satar, Bülent (The European Research Journal, 2019)
Vestibular neuritis in pregnancy is not often and it may be difficult for obstetricians and ENT doctors to evaluate a pregnant woman and to choose best treatment because of drug contrandications. A 33-year-old woman presented with vertigo at 28 weeks of the gestation. After physical examination and audiological and vestibular tests, vestibular neuritis was diagnosed, and the treatment was initiated. The patient completely recovered without any complaints; neither vestibular nor gynecological. There are few studies in the literature pointing out the evaluation of pregnant women with vestibular neuritis. However, there are safe ways to manage such patients.